PKM PENDAMPINGAN GURU DALAM PEMANFAATAN AI DAN MULTIMEDIA INTERAKTIF BERBASIS H5P EDPUZZLE DENGAN PENDEKATAN DEEP LEARNING DI KOTA BANDUNG - Acep Roni Hamdani; Dahlan, Taufiqulloh; Dheni Harmaen; Widaningsih; Adella Nur Annisa; Razan Rafiqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Educational transformation in the digital era requires teachers to master technological skills, particularly in utilizing artificial intelligence (AI) and interactive multimedia. Teachers are not only knowledge transmitters but also facilitators of learning who can provide innovative and adaptive learning experiences. This Community Service Program (PKM) was carried out with the aim of enhancing teachers’ competencies in Bandung City in using the H5P and Edpuzzle platforms integrated with the Deep Learning approach. The methods applied included needs analysis, training, mentoring, and continuous evaluation. A total of 30 junior high school teachers actively participated in this program over six months. The results showed that 85% of teachers were able to integrate AI into lesson planning, 78% successfully produced innovative learning media using H5P and Edpuzzle, and 72% demonstrated improved reflective abilities in implementing the Deep Learning Approach. This mentoring contributed to increased student participation, strengthened critical thinking skills, and improved learning motivation. These outcomes indicate that the integration of AI and interactive multimedia can serve as an effective strategy in realizing 21st-century learning that is collaborative, creative, and student-centered.